Architecture of ground floor (RFA-136_Rev E) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture (BUCG-ABC JV); Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF& DWG version of drawings.